A Noninvasive 3D Body Scanner and Software Tool towards Analysis of Scoliosis. (9th May 2019) - Roy, Susmita; Grünwald, Alexander T. D.; Alves-Pinto, Ana; Maier, Robert; Cremers, Daniel; Pfeiffer, Daniela; Lampe, Renée
Abstract : Purpose. Children with neurological disorders, such as cerebral palsy (CP), have a high risk of developing scoliosis during growth. The fast progression of scoliosis implies in several cases frequent clinical and X-ray examinations. We present an ionizing radiation-free, noncontacting method to estimate the trajectory of the vertebral column and to potentially facilitate medical diagnosis in cases where an X-ray examination is not indicated. Methods. A body scanner and corresponding analysis software tools have been developed to get 3D surface scans of patient torsos and to analyze their spinal curvatures. The trajectory of the vertebral column has been deduced from the body contours at different transverse sectional planes along the vertical torso axis. In order to verify the present methods, we have analyzed twenty-five torso contours, extracted from computer tomography (CT) images of patients who had a CT scan for other medical reasons, but incidentally also showed a scoliosis. The software tools therefore process data from the body scanner as well as X-ray or CT images. Results. The methods presented show good results in the estimations of the lateral deviation of the spine for mild and moderate scoliosis. The partial mismatch for severe cases is associated with a less accurate estimation of the rotation of the vertebrae around the vertical body axis in these cases. In addition, distinct torso contour shapes, in the transverse sections, have been characterized according to the severity of the scoliosis. Conclusion. The hardware and software tools are a first step towards an ionizing radiation-free analysis of progression of scoliosis. However, further improvements of the analysis methods and tests on a larger number of data sets with diverse types of scoliosis are necessary, before its introduction into clinical application as a supplementary tool to conventional examinations.